Serological surveillance of GI norovirus reveals persistence of blockade antibody in a Jidong community-based prospective cohort, 2014–2018 - Yu, Jing-Rong; Xie, Dong-Jie; Li, Jia-Heng; Koroma, Mark Momoh; Wang, Lu; Wang, Yu; Jing, Duo-Na; Xu, Jia-Yi; Yu, Jun-Xuan; Du, Hui-Sha; Zhou, Fei-Yuan; Liang, Zhi-Yan; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Herd immunity against norovirus (NoV) is poorly understood in terms of its serological properties and vaccine designs. The precise neutralizing serological features of genotypes I (GI) NoV have not been studied. To expand insights in vaccine design and herd immunity of NoVs, seroprevalence and seroincidence of NoV genotypes GI.2, GI.3, and GI.9 were determined using blockade antibodies based on a five-year longitudinal serosurveillance among 449 residents in Jidong community. Correlation between human histo-blood group antigens (HBGAs) and GI NoV, and dynamic and persistency of antibodies were also analyzed. Seroprevalence of GI.2, GI.3, and GI.9 NoV were 15.1-18.0%, 35.0-38.8%, and 17.6-22.0%; and seroincidence were 10.0, 21.0, and 11.0 per 100.0 person-year from 2014 to 2018, respectively. Blockade antibody positive to GI.2 and GI.3 NoV were significantly associated with HBGAs phenotypes, including blood types: A, B (excluding GI.3), and O+; Lewis phenotype: Leb+/Ley+ and Lea+b+/Lex+y+; and secretors. The overall decay rate of anti-GI.2 antibody was -5.9% /year (95% CI: -7.1%–4.8%/year), which was significantly faster than that of GI.3 [-3.6%/year (95% CI: -4.6%–2.6%/year)] and GI.9 strains [-4.0%/year (95% CI: -4.7%–3.3%/year)]. The duration of anti-GI.2, GI.3 and GI.9 NoV antibodies estimated by generalized linear model (GLM) was approximately 2.3, 4.2 and 4.8 years, respectively. In conclusion, enhanced community surveillance of GI NoV is needed, and even one-shot vaccine may provide coast-efficient health benefits against GI NoV infection.